Comparison of soil properties under tropical Acacia hybrid plantation and shifting cultivation land use in northern Vietnam. Issue 1 (2nd January 2017) - Hung, Trieu Thai; Doyle, Richard; Eyles, Alieta; Mohammed, Caroline
Abstract : Despite the common use of Acacia species in Vietnam, few studies have examined changes to total soil nitrogen (TN) and total soil carbon (TC) following the planting of Acacia mangium × Acacia auriculiformis ( Acacia hybrid) plantations (AH) on formerly eroded and degraded soils. We compared the impact of AH with adjacent fallow land within a shifting cultivation system (FSC) on various soil properties, including TC, TN, pH, bulk densities and particle-size distribution in 10 cm increments down to 30 cm for 25 paired sites in northern Vietnam. The results show that TN and TC concentrations in AH were significantly higher at all 10 cm depth increments when compared with FSC. Although both TC and TN decreased significantly with depth under both land uses, the C:N ratio only decreased in AH and not the FSC. However, there was a significant decrease in soil pH in AH at all depths (pH > 0.4) and this may potentially cause acid infertility issues. While the study has shown that planting Acacia hybrid is an excellent option for the improvement of TN and TC on degraded acidic Acrisols, mitigation of the associated acidification may be required.